ChemInform Abstract: Nortriterpenoids from Schisandra chinensis and Their Absolute Configurational Assignments by Electronic Circular Dichroism Study. Issue 28 (15th July 2014) - Sun, Han‐Dong; et al., et al.
Abstract Twelve new nortriterpenoids, namely wuweizidilactones J‐P [e.g. O (II)], schindilactones I‐K [e.g. I (I)], preschisanartanin N (III) and schisdilactone J, are isolated together with 23 known analogs.